Innovation - entrepreneurial competence - Muxitdinov Shuxrat Ziyavitdinovich; Khamidova Kamilla Ulugbekovna (Genius Publishing Group, 2022)
The main goal of modern education is to prepare a well-developed personality for society and the state socially adaptable to society. Therefore, it is important for future economists to develop technologies for the development of innovative entrepreneurial competence. Therefore, you first need to understand the essence of entrepreneurship. Then we need to analyze and understand the concept of innovation and competencies. In this article, all concepts are highlighted. The essence is very clear, it shows that entrepreneurship is a special economic activity specific to the market system, and it provides guidance on the development of this activity based on innovative creativity
Keywords: Entrepreneurship; economic activity; innovation; creativity